Bepridil exhibits anti‐leukemic activity associated with NOTCH1 pathway inhibition in chronic lymphocytic leukemia. Issue 4 (23rd March 2018) - Baldoni, Stefano; Del Papa, Beatrice; Dorillo, Erica; Aureli, Patrizia; De Falco, Filomena; Rompietti, Chiara; Sorcini, Daniele; Varasano, Emanuela; Cecchini, Debora; Zei, Tiziana; Di Tommaso, Ambra; Rosati, Emanuela; et al.
Abstract : Dysregulated NOTCH1 signaling, by either gene mutations or microenvironment interactions, has been increasingly linked to chronic lymphocytic leukemia (CLL). Thus, inhibiting NOTCH1 activity represents a potential therapeutic opportunity for this disease. Using gene expression‐based screening, we identified the calcium channel modulator bepridil as a new NOTCH1 pathway inhibitor. In primary CLL cells, bepridil induced selective apoptosis even in the presence of the protective stroma. Cytotoxic effects of bepridil were independent of NOTCH1 mutation and other prognostic markers. The antitumor efficacy of bepridil was associated with inhibition of NOTCH1 activity through a decrement in trans‐membrane and activated NOTCH1 protein levels with unchanged NOTCH2 protein levels. In a CLL xenotransplant model, bepridil significantly reduced the percentage of leukemic cells infiltrating the spleen via enhanced apoptosis and decreased NOTCH1 activation. In conclusion, we report in vitro and in vivo anti‐leukemic activity of bepridil associated with inhibition of the NOTCH1 pathway in CLL. These data provide a rationale for the clinical development of bepridil as anti‐NOTCH1 targeted therapy for CLL patients. Abstract : What's new? In search of new inroads against chronic lymphocytic leukemia, these authors turned to the NOTCH1 signalling pathway. Could inhibiting NOTCH1 help treat CLL? To find out, they first identified the calcium channel blocker bepridil as a NOTCH1 inhibitor. Next, they showed that bepredil induced apoptosis in isolated CLL cells, regardless of whether they bore NOTCH1 mutations. In mice bearing CLL cells, bepredil inhibited the proliferation of the tumor cells with no overt signs of toxicity. Thus, it seems advisable to pursue bepredil as a possible candidate for treating CLL.